A multimodalidade e os (multi)letramentos nas práticas de leitura com obras literárias digitais infantis - Hoffmann, Wesley Pinto (2023)
This research explores the theme of multimodality and (multi)literacies in reading practices with children's digital literary works. The overarching objective of this study is to apply and analyze reading practices based on multimodality to promote (multi)literacies among students in the early years of Elementary Education in a Public School. The theoretical foundation of this research draws on the work of Bakhtin (2015, 2016) and Voloshinov (2017) on discursive interaction, dialogical relations, discourse genres, and hetero discourse. The study also incorporates contributions from Sobral (2009), Colomer (2007), Cosson (2009), Pètit (2008), and Santaella (2012) on literary reading and different reader profiles. Additionally, the study draws on the propositions of Kalantzis, Cope, and Pinheiro (2020), Cazden et al. (2021), and Rojo (2012, 2013) on multimodality and (multi)literacies. The reflections of Coscarelli (2016) and Ribeiro (2021a, 2021b) on digital technologies and the new topographies of online texts are also considered as a contribution. This research adopts an applied nature and an exploratory approach regarding objectives. The technical procedures include bibliographic and action research, and the analysis employs a qualitative approach. The study's corpora comprise multimodal discursive genres organized by literacy sequences with two digital children's literary works from the Read for a Child Program from Fundação Itaú Cultural, made available in 2021. The results highlight the complexity of languages and support that guide the online texts created for developing (multi)literacies among students in the early years of schooling.